'Everything's a pound here, come and 'ave a look!': fandom and the car boot sale. Issue 17 (9th December 2022) - Hobbs, Simon
Abstract : Cutting through social, cultural and racial boundaries, the car boot sale appeals to those who are involuntarily excluded from mainstream commerce as well as groups who simply enjoy the freedom provided by a marginal retail space. Nicky Gregson and Louise Crewe's work from the late 1990s and early 2000s remains the most detailed study of the event, however changes to the social and cultural climate suggest that a reexamination of the sale's enduring appeal is long overdue. This article provides an updated assessment of how the car boot sale functions in an age of economic and social uncertainty and considers what specific pleasures and opportunities it offers attendees. The article combines the critical framework of fan studies with ethnographic research in order to discuss the ways 'booters' accumulate and exchange subcultural capital, engage in acts of collecting, and foster thriving communities through attendance, conversation and consumption. The article transforms the author's 'lived experience' into an examination of the complex cultural practices that occur throughout the car boot sale. In highlighting the role skill, knowledge and expertise play in the successful navigation of the event, the work draws attention not only to the manner in which boot fairs allow for feats of consumption and dispossession, but also how these acts enable attendees to develop and affirm significant and meaningful social identities.